Study on Zakat Management in ASEAN Countries - Atep Abdurofiq; Gilang Rizki Aji Putra (UIN Jakarta, 2025)
Zakat is an Islamic economic instrument that has a strategic role in improving social welfare and reducing economic inequality. Countries in the ASEAN region have diverse characteristics in terms of government systems, regulations, and institutions for zakat management. This article aims to examine the management of zakat in ASEAN countries by examining the aspects of regulation, institutions, mechanisms for collecting and distributing zakat, as well as the role of the state in its management. The research method used is a literature study with a descriptive-analytical approach to various literature sources, policy documents, and related research results. The results of the study show that zakat management in ASEAN countries shows a variety of models, ranging from systems that are formally integrated with the state to those that are managed semi-formally by non-governmental institutions. These differences are influenced by the legal, social, and political factors of each country. This study is expected to make an academic contribution and become a reference for the development of a more effective and sustainable zakat management policy in the ASEAN region.